Designing User Interface (UI) & User Experience (UX) Mobile Website Templates Digital Wedding Invitations - Siregar, Parlindungan; Haswanto, Naomi (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
Wedding invitations have been using the conventional way, with paper. Costs are not cheap, invitation printing takes a long time, and environmental issues in the use of paper. Wedding invitations no longer use paper media. Wedding invitations with user interface (UI) and user experience (UX) designs provide a new experience. UI/UX design is an important stage because it gives an initial impression to potential users. The design of digital wedding invitations uses a design thinking method approach which is consists of several stages, namely empathize, define, ideate, prototype, and testing. Empathize process using questionnaires and interviews. Respondents to the questionnaire were 92 people with an age range of 25 to 35 years and had a middle to upper economic level.Apart from being well educated, the respondents are active internet users. The results showed that respondents preferred the simple modern invitation design style. In the define process, users need several digital wedding invitation templates with international and traditional nuances. It is designed to be interactive, user friendly, and has features that can be customized. Furthermore, the ideation process is carried out based on the analysis of the define process, namely the design of mobile website templates for digital wedding invitations. Bride and groom are made easy with several template choices. The prototype process is carried out by getting the initial design, then testing it and doing it iteratively to get feedback from the bride and groom in order to get the digital wedding invitations that the bride and groom need.